الدلالات السياقية لاسم المفعول دراسة (صرفية نحوية) سورة الشعراء أنموذجا - أحمد خليفة; محمد عويني (University of Eloued جامعة الوادي, 2025)
تناولت هذه الدراسة الدلالات السياقية لاسم المفعول في النص القرآني، مع التركيز على سورة الشعراء، في محاولة لفهم تأثير السياق الصرفي والنحوي والدلالي على معناه وصياغته التعبيرية. أظهرت النتائج أن اسم المفعول ليس مجرد بنية صرفية جامدة، بل يمتلك حيوية دلالية تتفاعل مع مختلف أنواع السياق؛ إذ أبرز السياق الصرفي علاقته بالمشتقات الأخرى، وساهم السياق النحوي في تحديد موقعه ووظيفته التركيبية، بينما عَمّق السياق الدلالي المعنى وحقق انسجامه مع مقاصد الخطاب القرآني. كما تبين أن أسماء المفعول في سورة الشعراء، وخصوصاً في قصة موسى وفرعون، تعمل كأداة بلاغية تجمع بين الإحياء والتوكيد والتقرير، مما يعكس دقة وروعة النظم القرآني. وتشير الدراسة إلى أهمية الجمع بين التحليل الصرفي والنحوي والدلالي لفهم النص القرآني بشكل أعمق، مع ضرورة تعزيز الدراسات السياقية والتطبيقية، وإعداد معاجم وفهارس متخصصة بالمشتقات القرآنية لتسهيل البحث العلمي. This study examined the contextual semantics of the passive participle (ism al-maf‘ūl) in the Qur’anic text, with a focus on Surah Ash-Shu‘arā’, aiming to understand the impact of morphological, syntactic, and semantic contexts on its meaning and expressive formulation. The results showed that the passive participle is not merely a rigid morphological structure, but a form with semantic vitality that interacts with various types of context. The morphological context highlighted its relation to other derivatives, the syntactic context determined its grammatical position and structural function, while the semantic context deepened its meaning and ensured its coherence with the objectives of Qur’anic discourse. It was also found that the passive participles in Surah Ash-Shu‘arā’, especially in the story of Moses and Pharaoh, function as rhetorical tools combining vivacity, emphasis, and assertion, reflecting the precision and eloquence of Qur’anic composition. The study emphasizes the importance of integrating morphological, syntactic, and semantic analysis for a deeper understanding of the Qur’anic text, as well as the necessity of promoting contextual and applied studies and compiling specialized lexicons and indexes of Qur’anic derivatives to facilitate scholarly research.
مذكرة ماستر. أدب حديث ومعاصر. 2025
Keywords: اسم المفعول – السياق الصرفي – السياق النحوي – السياق الدلالي; Passive participle – Morphological context – Syntactic context – Semantic context – Surah Ash-Shu‘arā’ – Qur’anic rhetoric – Qur’anic studies – Linguistic derivatives